An Apparasail of Local Government on Mandatory Functions in Southwestern Nigeria (1999-2019) - David, Odewale Ayotunde; Marcellinus, Adepoju, Banji (American Journal of Social Sciences and Humanities, 2020)
This study appraises the performance of local government on their mandatory roles, especially in delivery of essential services to the populace at the grassroots in southwestern Nigeria between 1999 and 2019. Data for this study were collected through the primary and secondary sources. The study revealed that generally, local government has not been able to perform to expectation in discharging their mandatory functions due to fact that state governments had been diverting their attention more to concurrent functions than their mandatory functions. The study also revealed that the performance of local government in their mandatory functions has been a story of good to bad from year 1999 and 2019. The paper highlighted some recommendations and concluded that local government in southwestern Nigeria has significantly, though at a low ebb, performed their mandatory functions in provision of essential service to the populace between 1999 and 2019.